2019
DOI: 10.1136/bmjopen-2019-031918
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital and in-hospital delays to care and associated factors in patients with STEMI: an observational study in 101 non-PCI hospitals in China

Abstract: ObjectivesTo describe the prehospital and in-hospital delays to care and factors associated with the delays among patients with ST-segment elevation myocardial infarction (STEMI) in non-percutaneous coronary intervention (PCI) hospitals in China.Design, setting and participantsWe analysed data from a large registry-based quality of care improvement trial conducted from 2011 to 2014 among 101 non-PCI hospitals in China. A total of 7312 patients with STEMI were included. Prehospital delay was defined as time fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…However, the proportion of farmers in 2016-2018 in our study was similar to that of the CPACS-3 study (67.2% in central China in 2011-2014). [18] The proportion of prior stroke in our study was similar to national studies, such as the China Patient-centered Evaluative Assessment of Cardiac Events (China PEACE) (10.1% in central China in 2011-2015) [19] and China Acute Myocardial Infarction (CAMI) (8.6% in province level hospitals, 9.3% in prefecture level hospitals, and 9.6% in county level hospitals in 2013-2014) studies. [20] Similarly, the rate of prior MI was similar to that of the CAMI study (6.9% in province level hospitals, 7.0% in prefecture level hospitals, and 6.0% in county level hospitals in 2013-2014), but lower than the results of the China PEACE study (8.7% in central China in 2011-2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the proportion of farmers in 2016-2018 in our study was similar to that of the CPACS-3 study (67.2% in central China in 2011-2014). [18] The proportion of prior stroke in our study was similar to national studies, such as the China Patient-centered Evaluative Assessment of Cardiac Events (China PEACE) (10.1% in central China in 2011-2015) [19] and China Acute Myocardial Infarction (CAMI) (8.6% in province level hospitals, 9.3% in prefecture level hospitals, and 9.6% in county level hospitals in 2013-2014) studies. [20] Similarly, the rate of prior MI was similar to that of the CAMI study (6.9% in province level hospitals, 7.0% in prefecture level hospitals, and 6.0% in county level hospitals in 2013-2014), but lower than the results of the China PEACE study (8.7% in central China in 2011-2015).…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have shown that longer time to obtain informed consent of reperfusion, longer emergency department stay, doctors' concerns/ worries on patient safety/adverse events, and inadequate or no healthcare insurance to cover the cost may be related to prolonged FMC-to-fibrinolysis time. [18,22,23] Although our study showed that the use rate of thrombolytic therapy did not change and even the treatment delay was significantly prolonged, the use of specific thrombolytic agents increased, indicating the successful promotion of thrombolytic treatment for STEMI in Henan. [12] Urokinase was the most common thrombolytic agent used in 2011.…”
Section: Discussionmentioning
confidence: 86%
“…This delay was similar to low medical resources in China,[ 11 ] and in India where old age, rural residence, and symptom misinterpretation resulted in a significant delay in reaching the hospital,[ 12 ] whereas in Europe, the use of telemedicine for prehospital diagnosis and triage of patients directly to the catheter laboratory is feasible and allows 89% of patients living up to 95 km from the invasive center to be treated with PPCI within 120 min of the emergency medical service call. [ 13 ]…”
Section: Discussionmentioning
confidence: 70%
“…For STEMI patients, each hour of D2W delay is correlated with an increase in mortality of approximately 3–8% [ 3 , 18 ]. Although the care of STEMI patients has progressed substantially since CPC construction was popularized nationally [ 12 ], the D2W time can still be accelerated [ 14 , 15 ]. This study found that although both groups met the requirements of the CPC mechanism, there was a significant delay in the nursing handover group on FMC2BS and FMC2FAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies show that the introduction of the CPC mechanism has made significant progress in treating patients with STEMI in China [ 2 , 5 , 12 , 13 ]. However, several studies have also shown that many factors still contribute to delayed reperfusion in patients under the CPC mechanism [ 14 , 15 ]. This paper aims to investigate whether nursing handover delays the nursing efficiency of the process in the ED and thus affects patient prognosis under the CPC mechanism.…”
Section: Introductionmentioning
confidence: 99%